2020
DOI: 10.3389/fonc.2020.597434
|View full text |Cite
|
Sign up to set email alerts
|

Role of GPX4-Mediated Ferroptosis in the Sensitivity of Triple Negative Breast Cancer Cells to Gefitinib

Abstract: Gefitinib resistance in triple negative breast cancer (TNBC) is a growing important concern. Glutathione peroxidase 4 (GPX4) is a main regulator of ferroptosis, which is pivotal for TNBC cell growth. We investigated GPX4-mediated ferroptosis in gefitinib sensitivity in TNBC. Gefitinib resistant TNBC cells MDA-MB-231/Gef and HS578T/Gef were constructed and treated with lentivirus sh-GPX4 and ferroptosis inhibitor ferrostatin-1. GPX4 expression, cell viability and apoptosis were detected. Malondialdehyde (MDA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…Although numerous studies 10 , 11 , 12 , 13 have investigated the genes that might regulate cancer cell death through ferroptosis, their correlations with prognosis remain worth exploring. In this article, we explored the expression levels of 259 ferritinophagy‐related genes in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies 10 , 11 , 12 , 13 have investigated the genes that might regulate cancer cell death through ferroptosis, their correlations with prognosis remain worth exploring. In this article, we explored the expression levels of 259 ferritinophagy‐related genes in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Apatinib promotes ferroptosis in colorectal cancer by targeting ELOVL6/ACSL4 ( Tian et al, 2021 ). Inhibition of GPX4 can induce ferroptosis and enhance the sensitivity of triple-negative breast cancer to gefitinib ( Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione peroxidase 4 (GPX4) is the main regulator of ferroptosis, which is pivotal for triple-negative BC cell growth. Song et al [ 17 ] found that GPX4 expression was upregulated in gefitinib-resistant cells and knockdown of GPX4 in vitro and in vivo inhibited cell viability, reduced clonal formation, promoted apoptosis, and increased the cell sensitivity to gefitinib by promoting ferroptosis. Zhang and colleagues [ 23 ] recently reported that suppression of circRHOT1 inhibited cell proliferation, invasion and migration, and promoted apoptosis of BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis has been recently suggested as a promising target to inhibit tumor growth and trigger cell death, especially in malignant tumors that are resistant to traditional therapies [ 16 ]. Roles and molecular mechanisms of ferroptosis in BC have been investigated in several studies [ 17 , 18 ]. Recent studies have investigated the key mechanisms regulating ferroptosis in BC [ 19 ].…”
Section: Introductionmentioning
confidence: 99%